Berotralstat: A data review of a novel oral medication for the treatment of hereditary angioedema (Canadian Allergy & Immunology Today, 2024)
The treatment of hereditary angioedema (HAE) has progressed significantly over the last decade. HAE is an autosomal dominant condition that is bradykinin mediated and affects approximately 1 in 50,000 people. This condition continues to challenge allergists/immunologists (A/I) in promptly managing the disease to reduce attacks of potentially life-threatening angioedema, while improving quality of life in a population in which disease activity tends to increase with age. Notably, delays in diagnosis may reach up to 8 years from initial presentation. The impact of HAE extends beyond the patient, and can affect their caregivers, owing to the fear of acute attacks, which can lead to absenteeism both at school and in the workplace and ultimately negatively impact quality of life and career productivity.